PENGARUH SELF LEADERSHIP, KECERDASAN SOSIAL, EMPLOYEE ABILITY TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN DINAS PENGENDALIAN PENDUDUK, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA SURABAYA - Eva Rachmawati; Siti Mujanah; Wiwik Retnaningsih (Universitas 17 Agustus 1945 Surabaya, 2018)
The purpose of this study is to analyze The Influence of Self leadership, Social intelligence,Employee ability influence on organizational commitment and Employee Performance of DinasPengendalian Penduduk, Pemberdayaan Perempuandan Perlindungan Anak Surabaya. Respondents ofthis study were 80 employees. he method of data collection in this study is a survey method with aninstrument questionnaire distributed to respondents. Data was analysis used SmartPLS package. And theresult of this research showed were that Self LeadershipÂ has not significant influence on commitmentorganizational, Social intelligence and employee ability has a significant effect onÂ organizationalcommitment, and Self Leadership, Social intelligence, andÂ Employee ability have significant effectemployee performance, The Organizational commitment has a significant effect on employeeperformance Dinas Pengendalian Penduduk, Pemberdayaan Perempuandan Perlindungan Anak Surabaya.Keywords: Self leadership, Social Intelligence, Employee Ability, Organizational Commitment, andEmployee Performance